2021
DOI: 10.46481/jnsps.2021.265
|View full text |Cite
|
Sign up to set email alerts
|

Goodness of Fit Test of an Autocorrelated Time Series Cubic Smoothing Spline Model

Abstract: We investigated the finite properties as well as the goodness of fit test for the cubic smoothing spline selection methods like the Generalized Maximum Likelihood (GML), Generalized Cross-Validation (GCV) and Mallow CP criterion (MCP) estimators for time-series observation when there is the presence of Autocorrelation in the error term of the model. The Monte-Carlo study considered 1,000 replication with six sample sizes: 30; 60; 120; 240; 480 and 960, four degree of autocorrelations; 0.1; 0.3; 0.5; and 0.9 an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 23 publications
1
2
0
Order By: Relevance
“…(See Figures 1 and 2). This discovery is in agreement with the Monte-Carlo experiments' results from [2], [18], [19], [24], [25], [26], and [27]. It is also noticed that the predictive mean square error of the proposed smoothing method (PSM) goes to zero at a faster rate in the presence of autocorrelation error than the PMSE of the other smoothing methods considered in this study (see Tables 3 and 4).…”
Section: Discussionsupporting
confidence: 91%
“…(See Figures 1 and 2). This discovery is in agreement with the Monte-Carlo experiments' results from [2], [18], [19], [24], [25], [26], and [27]. It is also noticed that the predictive mean square error of the proposed smoothing method (PSM) goes to zero at a faster rate in the presence of autocorrelation error than the PMSE of the other smoothing methods considered in this study (see Tables 3 and 4).…”
Section: Discussionsupporting
confidence: 91%
“…Furthermore, agricultural products are subject to meteorological, ecological, and environmental variation [8,[10][11][12][13][14], wherein planetary and chronological qualities have a very important link over the environment by applying time series modeling i.e ARIMA model [5,[15][16][17][18]. International heating impacts, according to [19][20][21][22], contribute to the development of the atmospheric structure; nevertheless, this effect is on the upcoming alterations in the cli-matic growth of the environment, where the occurrence and size of diverse happenings affect the growth of any region [6,23]. According to the international heating effect, an increase in temperature and a decrease in rainfall lead to famine in any environment; nevertheless, this contributes to multiple pressures on food as a result of reduced rainfall and an increase in environmental temperature [17].…”
Section: Introductionmentioning
confidence: 99%
“…According to research, the mobile communication sector supported approximately 500,000 employment in Nigeria in 2017 and added $21 billion, or 5.5% of the total Gross domestic product (GDP) to the nation's GDP. The study by [6] claims that the digital economy also contributed $1.8 billion in taxes, or 16% of all government tax collection in Nigeria. It is confirmed that Nigerian daily life has improved as a result of the government, industry, and consumer embrace of digital services.…”
Section: Panel Data Regression Voice Over Internet Protocol (Voip) To...mentioning
confidence: 99%
“…Having these qualities makes a model a proper impacts model. Two strategies are used to appraise condition (6). The coefficient are known as fixed impacts, and the expression "fixed impacts" are usually alludes more to the assessment interaction and different assumption that we make than it does to whether the coefficient are random or fixed.…”
Section: Fixed Effect Modelmentioning
confidence: 99%